Studying the effect of summer and winter seasons on some physiological and biochemical characteristics of blood in one-humped camels in Nineveh Governorate - Ibrahem, Mohammad Salem (Journal of agricultural, environmental and veterinary sciences, 2023)
This study was conducted during the summer of 2018 and winter of 2019 in the Tel Abta region (Nineveh - Iraq) on a number of males and females of one-humped camels to study the effect of seasonal (summer and winter) and animal sex (males and females) on some physiological and biochemical blood characteristics. The summer season had a significant effect (P  0.05) on the increase in serum protein, globulin, urea, cholesterol, sodium, and Erythrocyte Sedimentation Rate compared with the winter season. The winter season had a significant effect (P  0.05) on the increase in hemoglobin concentration, compacted cell volume, white blood cell count and ALT enzyme concentration in the blood serum compared with the summer season. The results of the study of animal sex (males and females) indicated that there was a significant effect (P  0.05) in the studied traits, where we noticed a high concentration of blood glucose, globulin and serum potassium for males compared to females. And the high concentration of protein, albumin, urea, ALT enzyme, triglycerides and serum cholesterol in females compared to males.
Keywords: Camels; Blood; year seasonal; animal sex